The Concept of Dalihan Na Tolu in Bataknese Community: Semiotic Analysis - Agung Yoan Toti Napitupulu; Muhammad Kiki Wardana; Bima Prana Chitra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
Dalihan Na Tolu is a philosophy of life for the community which is the basis for the rules of the Batak community in society. Dalihan Na Tolu’s consists of three main parts, namely somba marhula-hula, elek marboru, and manat mardongan tubu. This thesis aims to analyze thesemiotics signs contained in the Batak Toba wedding ceremony, namely martuppol which is included in Dalihan Na Tolu, as well as the meaning of the sign through the symbolic relationship between the signifier and the signified. This study uses a qualitative descriptive method with data sources in the form of interviews with people related to the martuppol event and the data used in this study are text and images. The theory used to analyze the data is the theory proposed by Odgen and Richard about the semiotic triangle. The findings of this study consist of signs found in the martuppol event, there are 4 important signs found in the event. The findings of this study are expected to be a useful resource in other research and for the development of semiotic studies of commercial works.